Greenhouse Covering Material Overall Heat-transfer Coefficient Determination Using Contour Plots - Yuta Ohashi; Ryota Tsuchiya; Masahisa Ishii; Makio Hayashi (HortScience)
Improving greenhouse heat-insulating performance requires covering materials with low overall heat-transfer coefficients. We constructed a contour plot using equations relating this coefficient to longwave radiation absorptance under different outdoor downward longwave radiation levels. It revealed that the coefficient ranged from 4.7 to 7.7 W·m−2·K−1, decreasing with increasing downward longwave radiation and longwave radiation absorptance. This method facilitates rapid estimation of overall heat-transfer coefficients under different downward longwave-radiation levels, based on longwave-radiation absorptance.